Le radici culturali e letterarie straniere del motivo di travestimento nel dramma croato preottocentesco - Čale Feldman, Lada (Array, 1999)
Cross-dressing, as a culturally scandalous performative image which blurs the boundaries of accepted social perception of gender identities, is a rare one in the corpus of old Croatian drama. The aim of this study is to analyse cross-dressing as it is inscribed in the dramatic structure and to regard it as a sematically productive and poetically valued topos, especially in the context of complications that arise in performative interpretation of an all-male production.